EVALUATION OF CARDIAC AUTONOMIC CONTROL DURING SIX-MINUTE WALK TEST IN OBESE AMONG MEDICAL FACULTY STUDENTS OF UDAYANA UNIVERSITY - Nugiaswari, Putu Primeriana; Laksmi, Ni Made Dharma; Ferdiyanthi, Ayu Putu Harina; Adiputra, Kristianto Yusi Ngurah Prana (E-Jurnal Medika Udayana; Vol 14 No 6 (2025): E-Jurnal Medika Udayana, 2025)
Background: Increased body mass index (BMI) has been widely studied in relation to various chronic diseases. BMI tends to increase in most individuals from adolescence to young adulthood, suggesting that early increases in BMI may contribute to the development of cardiovascular disease later in life. However, studies directly linking BMI to cardiovascular disease risk factors, especially in adolescents and young adults, are limited. Early intervention is crucial to address this issue, as proactive measures can help prevent future cardiovascular events. Delay in addressing obesity can result in severe consequences, including death. Functional capacity serves as an objective measure to evaluate a person's ability to perform daily activities, especially in patients with certain medical conditions. In the case of obese patients, assessing functional capacity is essential to understand their physical limitations and guide interventions. One reliable indicator of functional capacity is the Six Minute Walk Test (6MWT), which measures the distance walked within six minutes and reflects the patient's ability to perform routine activities. Results: Measurements were carefully taken, and conditions before and after the six-minute walking test were closely monitored. Heart Rate Variability (HRV), also known as RR interval, represents autonomic control of the heart and is defined as the time interval between two consecutive R waves (the wave with the highest amplitude). The study included a total of 75 participants, consisting of 35 men (46.7%) and 40 women (53.3%). Conclusion: Significant results were obtained on HRV. The results showed that the higher the body mass index, the lower the HRV (p=0.000). Keywords: Obesity, autonomic cardiac control, 6MWT